Association Mapping for Improvement of Quantitative Traits in Plant Breeding Populations - Rosyara, Umesh R; Joshi, Bal K (Nepal Journal of Biotechnology, 2012)
DNA-based molecular markers have been extensively utilized for mapping of genes and quantitative trait loci (QTL) of interest based on linkage analysis in mapping populations. This is in contrast to human genetics that use of linkage disequilibrium (LD)-based mapping for fine mapping of QTLs using single nucleotide polymorphisms. LD based association mapping (AM) has promise to be used in plants. Possible use of such approach may be for fine mapping of genes / QTLs, identifying favorable alleles for marker aided selection and cross validation of results from linkage mapping for precise location of genes / QTLs of interest. In the present review, we discuss different mapping populations, approaches, prospects and limitations of using association mapping in plant breeding populations. This is expected to create awareness in plant breeders in use of AM in crop improvement activities. Key words: Association mapping; plant breeding; DNA marker; quantitative trait loci DOI: http://dx.doi.org/10.3126/njb.v2i1.5686 Nepal Journal of Biotechnology Jan.2012, Vol.2(1): 72-89